2022
DOI: 10.18844/wjet.v14i3.7193
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the education landscape caused by COVID-19: Opportunities and challenges from UAE perspective

Abstract: The study aim is to identify the opportunities for the United Arab Emirates (UAE) educational sector during COVID-19. A survey was conducted among a sample of 100 teachers from 20 UAE higher education institutions. Teachers use online learning tools that cannot fully provide the benefits of face-to-face meetings with students. The research methodology is based on primary and secondary data analysis. Teacher questionnaire was formed; it contains 9 questions on distance learning actualization in a pandemic. Only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the early stages of the pandemic, Azorín (2020) highlighted COVID‐19's exacerbating effects on the Spanish education system. The study pointed to several dynamics which fairly encapsulate a global picture, including high rates of socioeconomic segregation (Kuzmanic et al., 2023; Macías León & Del Pino‐Brunet, 2023; Praharaj et al., 2023); overcrowded classrooms (Graham, 2023); obsolete curricula (Abdallah & Alriyami, 2022); and teachers' digital competency, or lack thereof (Basilotta‐Gómez‐Pablos et al., 2022). As early as (2021), UNESCO reported that COVID‐related school closures have been linked to students' stunted cognitive and psychosocial development and other similarly troubling trends.…”
Section: How Should We Critically Look At and Meet Desired Outcomes A...mentioning
confidence: 97%
“…In the early stages of the pandemic, Azorín (2020) highlighted COVID‐19's exacerbating effects on the Spanish education system. The study pointed to several dynamics which fairly encapsulate a global picture, including high rates of socioeconomic segregation (Kuzmanic et al., 2023; Macías León & Del Pino‐Brunet, 2023; Praharaj et al., 2023); overcrowded classrooms (Graham, 2023); obsolete curricula (Abdallah & Alriyami, 2022); and teachers' digital competency, or lack thereof (Basilotta‐Gómez‐Pablos et al., 2022). As early as (2021), UNESCO reported that COVID‐related school closures have been linked to students' stunted cognitive and psychosocial development and other similarly troubling trends.…”
Section: How Should We Critically Look At and Meet Desired Outcomes A...mentioning
confidence: 97%
“…2 The quality and effectiveness of Duolingo and Memrise applications have already been subject to research within the scientific community. There are scientific articles and publications exploring their effectiveness and impact on learning and language skill development (Kuşçu, 2019;Arifin, 2020;Aulia et al, 2020;Issa et al, 2021;Abdallah and Alriyami, 2022). This provides support for including these applications in foreign language research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In present era of globalization and informatization, innovative technologies penetrate all spheres of human life, including education (Chang, Chou, Chuang, Li, & Tsai, 2023;Yelbayeva et al, 2017). Digitalization caused a rapid transition from traditional education to novel learning methods, tools, and technologies (Abdallah & Alriyami, 2022). In this new reality, however, students appear to be more tech-savvy than their teachers (Mikidenko & Storozheva, 2021).…”
Section: Introductionmentioning
confidence: 99%